Esquemas interpretativos e os condicionantes institucionais e relacionais da adoção de práticas de gestão financeira em organizações - Luz, Andréia Ribeiro da (2012)
The present study describes and explains how the interpretive schemes and relationships influence the adoption of financial management practices by manufacturing industries in the face of environmental pressures. Among the existing organizational practices, it was chosen the financial management practices to determine if the phenomenon of financialization of wealth is present in organizations such as recurring practice. And it was used the institutional perspective to analyze the financial area. The field of research was composed of small, medium and large manufacturing companies located in Paraná state. This is descriptiveexplanatory study based on concepts developed in the field of sociological institutional theory and economic sociology. The search strategy adopted was the survey method with a crosssection perspective with the evaluation of 110 manufacturing companies. The level of analysis was the organization analysis and the organizational unit of analysis was the financial leaders of companies. Data collection occurred in three phases: first, documentary evidence; second, interviews with experts in the area; third, questionnaires to financial managers. It was used content analysis technique to qualitative analysis and statistical techniques (descriptive statistics, factorial analysis, regression and logistic regression) to quantitative analysis. The results showed the effect of environmental and technical pressures on the financial management practices adopted, as well as the effect of the organizational values and relationships on the relationship between environmental pressure and practices. The results showed that the phenomenon of financialization of wealth in Brazil is still incipient, being at the stage of theoretical discourse, not being institutionalized in the companies analyzed in this study. However, the results presented the "intention", in other words, it presents a slight tendency to appreciate financial aspects instead of production aspects.